Generation and characterization of protective antibodies to Marburg virus. Issue 4 (19th May 2017) - Froude, Jeffrey W.; Pelat, Thibaut; Miethe, Sebastian; Zak, Samantha E.; Wec, Anna Z.; Chandran, Kartik; Brannan, Jennifer Mary; Bakken, Russell R.; Hust, Michael; Thullier, Philippe; Dye, John M.
ABSTRACT: Marburg virus (MARV) and Ebola virus (EBOV) have been a source of epidemics and outbreaks for several decades. We present here the generation and characterization of the first protective antibodies specific for wild-type MARV. Non-human primates (NHP), cynomolgus macaques, were immunized with viral-replicon particles expressing the glycoproteins (GP) of MARV (Ci67 isolate). An antibody fragment (single-chain variable fragment, scFv) phage display library was built after four immunogen injections, and screened against the GP1-649 of MARV. Sequencing of 192 selected clones identified 18 clones with distinct VH and VL sequences. Four of these recombinant antibodies (R4A1, R4B11, R4G2, and R3F6) were produced in the scFv-Fc format for in vivo studies. Mice that were challenged with wild-type Marburg virus (Ci67 isolate) receiving 100 µg of scFv-Fc on days −1, 1 and 3 demonstrated protective efficacies ranging from 75–100%. The amino-acid sequences of the scFv-Fcs are similar to those of their human germline counterparts, sharing an identity ranging between 68 and 100% to human germline immunoglobulin. These results demonstrate for the first time that recombinant antibodies offer protection against wild-type MARV, and suggest they may be promising candidates for further therapeutic development especially due to their human homology.